CYTOTOXIC ACTIVITY OF BASIL SEEDS( Ocimum baslicum L) EXTRACTS ON SOME BREAST CANCER CELL LINES ( IN VITRO) - Ayeda M.M,; J. M. Awda, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
In this study, four types of basil seed extracts were used, being cold aqueous extract, hot aqueous extract, petroleum ether extract, and methanolic extract.Nine concentrations (10000, 5000, 2500, 1250, 625, 312.56, 156.25, 78.125, 39.0, 0.0) µg/ml were used to study the extracts cytotoxicity against two breast cancer cell lines MCF7 and AMJ13 beside REF cell line as normal cells. The methanol extract showed the highest inhibition rate of 64.4% on MCF7 cell line at concentration of 1250 µg/ml and 42.4% on AMJ13 cell line at a concentration  of 39.0 µg/ml with significant difference as compared to  control  sample during the 72hr exposure period. While the petroleum ether extract showed a lower inhibition rate of 16.02% at a concentration of 78.1 µg/ml on MCF7 cell line  and 35.3 % at a concentration of 312.5 µg /ml on AMJ13 cells during a 72hr exposure period, compared with the two aqueous extracts which showed a slight effect compared to the control. The cold aqueous extract showed the slight effect of 24.4% at a concentration of 5000 µg/ml on AMJ13 cell line and no toxicity was shown on MCF7 cells. All extracts showed no effect on REF normal cells. In all effective concentrations the basil seed extracts caused a damage to the DNA that cannot be repaired, and thus the cells are heading to programmed death. This effect on the genetic material was studied using the comet assay and mitotic index.